The knowledge of children on tooth care: A qualitative and quantitative approach - Dos Santos Pacheco, Karina Tonini; Junior, Manoelito Ferreira Silva; Arcieri, Renato Moreira [UNESP]; Garbin, Artênio José Isper [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (EDIPUCRS, 2016)
Objective: To assess the knowledge of children who participated in an Oral Health Educational Program (OHEP) on the subject tooth care. Methods: The study was conducted on children aged 6 to 9 years, participating in activities developed twice a week in an OHEP during one academic year. Data were collected by redactions and drawings. Drawings were analyzed according to the methodology proposed by Taylor, Roth and Mayberry. The redactions were analyzed according to the citation of hygiene items and the content presented, taking as theoretical reference the content analysis of Bardin. Results: All children mentioned the toothbrush and toothpaste as oral hygiene items. As a negative aspect to oral health, candies were mentioned by 74.4% of children, with greatest citations of confections, chewing gum and lollipop. All redactions mentioned aspects of toothbrushing, such as frequency, technique and/or quality. The consequences of not caring were also present, and were related to dental caries, edentulism, halitosis, pain, and personal relationship. The reason for caring was also mentioned, and was related to the importance of teeth for the individual, and clean, healthy and bright teeth. Conclusion: The children presented satisfactory understanding on tooth care, evidencing the importance of oral health education programs for this population.
Keywords: Health Education; Health Promotion; Oral Health